Cultivating resilience in college students with a foster care background. Issue 2 (15th March 2021) - Cheung, Justine R.; Lietz, Cynthia A.; Carpenter, Breanna M.; Sitz, Erin; Lietz, Bryan C.
ABSTRACT: Taking a resilience approach, this study sought to understand what strengths helped young people with foster care experience successfully transition during their first year in college. In-depth, narrative interviews were conducted with a sample of students with foster care experience who had successfully completed their first year of college demonstrating an important milestone of retention. Findings suggest that while the extent of the problems experienced by these students are unique, the process of coping and adaptation that emerged from their stories may have implications for other college students who are at risk of poor outcomes in post-secondary education. Findings offer important implications for colleges and universities as they seek to support groups of students such as those with a foster care background with complex challenges as they transition to college. Considering campus-based support programs for current or former foster youth are typically either managed by higher education or social work programs, findings offer implications for both disciplines.